The Court of Queen's Bench of Manitoba, 1870-1950 : a biographical history - Brawn, Dale, 1948- (Osgoode Society for Canadian Legal History., 2006)
This fascinating study offers an intimate look at personalities ranging from prime ministers to members of the bench and both senior levels of government.